Carbon Tariffs: An Analysis of the Trade, Welfare and Emission Effects - Mario Larch; Joschka Wanner (Center for Economic Studies and ifo Institute (CESifo), 2014)
Carbon tariffs are one prominently discussed environmental policy. The proponents stress the carbon tariffs' ability to mitigate the potential negative effect of environmental-friendly production on competitiveness, to avoid carbon leakage and to reduce world carbon emissions. We analyze the effects of carbon tariffs on trade, welfare and carbon emissions in a multi-sector, two-factor gravity model. The introduction of carbon tariffs reduces welfare in most countries, but the effect tends to be more pronounced in poorer countries. Further, carbon emissions are massively shifted from these countries to richer countries. Most remarkably, world carbon emissions increase by 0.49 percent in the investigated counter-factual scenario, with a bootstrapped 95% confidence interval of [0.44, 0.55].
Keywords: F14; F18; Q56; 330; carbon tariffs; environmental policy; gravity model